Performance of Linear Electric Drive at Localizing of Dust Explosions - Rinkeviciene, R.; Savickiene, Z.; Poska, A. J. (Elektronika ir Elektrotechnika, 2012)
Performance of dust explosion localizing systems with fire blocking dampers, whose moving element is aligned with linear induction motor (LIM) secondary element, is considered. It is stated experimentally, that dust explosion wave can deform moving element and it will begin to graze LIM inductor and could be lost control of ADELS. Therefore additional sliding and rolling bearings should be mounted in the active zone of LIM; sliding index of those differs from that of damper directives. Simulation of linear induction drive with load, depending on dust explosion pressure and degree of deformation of damper moving element with indicated capability of damper with the additional bearings in LIM active zone to block even strong primary explosion sources. Ill. 7, bibl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1831